Transnationalism, Identity and Material culture in the Finnish-Lithuanian and Greek-Lithuanian Families - Akvile Motuzaite (Bulgaria, 2022)
Ethnically mixed marriage can be of different types and in various cultural circumstances. Union between members of different ethnic majorities refers to different partners’ nationality and identity. Such family’s life combines elements of different cultural swirl and obtains transnational attribution. This condition usually is evoked when one partner moves abroad into the husband/ wife’s social circle and more or less different cultural environment.
Family’s home carries different cultural meanings and can be seen as a reflection of family identities. A woman usually is the main home creator and developer of its cultural side that involves various artefacts. In the research cases of mixed families the majority of women were Lithuanian living with Finnish and Greek husbands in urban residences of Finland and Greece. The research focused, if and how such families’ home environment reflects different partners’ ethnic identities and cultural elements referring to it. The combination of different material elements and artefacts signals traces of transnational family’s culture.
Research results reveal that some Lithuanian women find it important to display objects and artefacts referring to their ethnic identity and culture. These items do not necessarily indicate mere different nationality but demonstrate cultural elements that make a link to Lithuania – its culture and native social circle: family and friends. The artefacts mentioned by women and noticed at homes can be preliminary grouped according to their function as follows: aesthetic (e.g. art pieces like reproductions of M. K. Čiurlionis paintings), symbolic (e.g. a flag of Lithuania), representative (e.g. photo-albums about Lithuania, different Lithuanian food products for treating), sentimental (e.g. Lithuanian native family belongings, photos), educational (e.g. Lithuanian books for children). Such and similar cultural elements strengthen aspect of transnationalism in the mixed family’s home environment and life.
Cultural Heritage in Migration